2014
DOI: 10.1002/hed.23569
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of the proliferation marker Ki‐67 in laryngeal carcinoma: Results of the Accelerated Radiotherapy with Carbogen Breathing and Nicotinamide phase III randomized trial

Abstract: Patients with laryngeal carcinomas with high proliferative activity are at increased risk of regional and distant metastases formation. This risk can be reduced by treatment with ARCON.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 17 publications
(29 reference statements)
0
23
0
Order By: Relevance
“…It also enhanced locoregional control and disease-free survival in anemic laryngeal cancer patients in addition to their quality of life after the treatment [106,107]. Likewise, ARCON was found to improve prognosis in patients with highly proliferative laryngeal cancers (detected with Ki-67 immunohistochemistry) [102]. In urinary bladder cancer, Hoskin et al performed a phase II clinical trial where ARCON was found to be relatively safe and well tolerated; in addition, the latter enhanced local regional control and improved overall survival [108,109].…”
Section: Soft Tissue/fibrosarcoma)mentioning
confidence: 89%
“…It also enhanced locoregional control and disease-free survival in anemic laryngeal cancer patients in addition to their quality of life after the treatment [106,107]. Likewise, ARCON was found to improve prognosis in patients with highly proliferative laryngeal cancers (detected with Ki-67 immunohistochemistry) [102]. In urinary bladder cancer, Hoskin et al performed a phase II clinical trial where ARCON was found to be relatively safe and well tolerated; in addition, the latter enhanced local regional control and improved overall survival [108,109].…”
Section: Soft Tissue/fibrosarcoma)mentioning
confidence: 89%
“…Ki-67, a gene located on chromosome 10, can detect a nuclear protein in the nuclear matrix of proliferating cells and its function has been shown to be associated with mitosis. In particular, closely associated with tumor cell proliferation ( 16 18 ). Currently, however, Ki-67 expression and its function in luminal breast cancer has not been completely elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] The evaluation of Ki-67 expression has been performed using different cut-offs, varying from 10% to 60%. [17][18][19][20][21] Therefore, Ki-67 expression was evaluated using the median staining percentage (49%). Expression of β-Catenin was scored on both membranous as well as cytoplasmic staining.…”
Section: Evaluation Of Immunohistochemical Stainingmentioning
confidence: 99%